Performance During “M-Form” Reorganization and Recovery Time: The Effects of Prior Strategy and Implementation Speed - Lamont, Bruce T.; Williams, Robert J.; Hoffman, James J. (Academy of Management Journal, 1994)
Taking a different tack from previous work on the performance effects of ?M-form? adoption, this study examined performance deterioration during reorganization periods and the subsequent time required for performance to recover to prereorganization levels. Prior strategy and implementation speed were found to affect both transition performance and recovery time.